Pengaturan Irigasi Berbasis Iot Untuk Persawahan - Farlan Rahmadhonu; yani prabowo; Swasti Broto; Siswanto Siswanto (Universitas Budi Luhur, 2020)
Water is the most important part of the agricultural system that cannot be replaced by other media, the problem is that on agricultural land with a limited amount of water this water must be divided equally by all farmers. Often there are disputes between farmers over fighting for water. In the traditional irrigation system, there is generally someone appointed by the residents to manage irrigation in the fields. This officer will open the lid of the irrigation system by hoeing the rice fields and waiting for the water to fill the rice fields to a predetermined limit. But there are frequent water thefts by residents who can't wait to queue. This study aims to design an automatic control device for water flow in rice fields that can make it easier to provide water to the rice fields. The design of the system begins with the use of an Arduino Uno microcontroller, as a system controller, a servo motor to open and close the floodgates, NodeMCU for communication with Telegram and a water level to set a water volume level limit in a rice field can be formulated by measuring the area of land multiplied by the water level. Officers can provide instructions via Telegram installed on the smartphone, so opening and closing the floodgates can be done remotely. With this system, it can help officers and farmers to manage the water supply schedule without having to go to the fields to open rice fields and wait for the water to reach its maximum limit. This system works well if it is supported by a good irrigation network infrastructure